Analysis of 4G mobile network coverage in UTeM technology campus - Zahariah Manap; Anis Suhaila Mohd Zain; Rahaini Mohd Said; Shawn Shivaneson Balakirisnan (Institute of Advanced Engineering and Science, 2020)
This paper proposes an analysis of the coverage performance of 4G cellular services in UTeM Technology Campus. The performance of the cellular services is presented as the network’s coverage profile which is based on the received signal strength indicator (RSSI). The area under study is virtually divided into 64 grid points where the average RSSI measurements are captured by using an open source software namely G-Mon. The measured values are mapped into the network coverage profile which represents the signal reception quality at each of the grid points. A statistical analysis called Two-Way ANOVA is performed to investigate the correlation of the performance of 4G cellular services in UTeM Technology Campus with the mobile phone brands and service operators. Based on the analysis, it is found that the signal reception in outdoor areas are better than that of indoor areas. In addition, the analysis shows that the propagation loss and signal degradation are two factors that contribute to the 4G services’ performance in UTeM Technology Campus.